Evaluasi Perikanan Tangkap di Sungai Rungan Kalimantan Tengah - Ummi Suraya; - Haryuni (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
The aim of this study was to obtain data on the selectivity of some fishing gear size several types of fish, the mortality parameter several species of fish, fishing season and yield of some fishing gear. The information is expected to provide fill for the management of Rungan river fishery. Research carried out for 4 months, i.e. May to September 2012. Fish sampling techniques performed in a random way and the records maintained by the respondent. The catch from Upper River shows lower yields than from Lower River and estuary. In terms of size selectivity of the fishing gear, fishing gear Selambau jeopardize the sustainability of fish resources, especially for large fish species such as Baung and Haruan, due to the small size when not had time to reproduce has been caught. Value of the rate of catch for large fish that is high enough are: E = 0.71 for Gabus and 0.57 for Baung . As for small fish such as tambakan, value of catch rate is still low E = 0, 41